Pelatihan Pemanfaatan Media Fokusky Bagi Guru SMK di Tinambung Kabupaten Polewali Mandar - Nurlaela Nurlaela; Ashar Pramono; Djuanda Djuanda; Muhsin Z Muhsin; Muhammad Haristo Rahman (Sakura Digital Nusantara, 2023)
One of the efforts to realize the function of national education is to create conditions and atmosphere that can foster students' interest in learning. Solusiky is software for internet-based presentations. Apart from presentations, Solusiky can also be used as a tool to explore and Solusiky is superior because this program uses Zooming user interface (ZUI), which allows Solusiky users to zoom in and out on presentations. There are no presentation media options other than Power Point. The problems that occur are (1) Students tend to get bored with the presentation media currently used. (2) There is no training on new presentation media. (3) Lack of knowledge on how to use the Solusiky application. PKM activities can increase the knowledge and insight of partners or teachers regarding the use of Solusiky learning media and become a reference for several learning media options that can be used. Implementation of community service hybrid learning media training for teachers at Tinambung Vocational School, Polewali Mandar Regency, had a good impact